Perancangan Sistem Informasi Produk Pada Percetakan Fauzan Berbasis Web - Ahmad Fauzan Rizaldi; Fadil Ardiansyah; Muhammad Rizal; Saprudin (CV. Shofanah Media Berkah, 2023)
Printing is an industrial process for mass-producing writing and images, especially with ink on paper using a printing press. Every day billions of printed materials are produced, including books, calendars, newsletters, magazines, newspapers, posters, wedding invitations, brochures, and more. This is because printing results can quickly communicate thoughts and information to millions of people. Printing is considered one of the most important and influential inventions in the history of human civilization. Fauzan Printing is an individual business engaged in printing services located in Tangerang Regency, Banten Province. Products produced from Fauzan Printing are wedding invitations, banners, pins, x-banners, posters, and so on. This study aims to help promote website-based product sales, to determine efficiency for consumers who view products and order them online.